Antiadhesive and antibiofilm activity of hyaluronic acid against bacteria responsible for respiratory tract infections. Issue 10 (4th April 2014) - Drago, Lorenzo; Cappelletti, Laura; De Vecchi, Elena; Pignataro, Lorenzo; Torretta, Sara; Mattina, Roberto
<x xml:space="preserve">Abstract</x> To address the problem of limited efficacy of existing antibiotics in the treatment of bacterial biofilm, it is necessary to find alternative remedies. One candidate could be hyaluronic acid; this study therefore aimed to evaluate the in vitro antiadhesive and antibiofilm activity of hyaluronic acid toward bacterial species commonly isolated from respiratory infections. Interference exerted on bacterial adhesion was evaluated by using Hep‐2 cells, while the antibiofilm activity was assessed by means of spectrophotometry after incubation of biofilm with hyaluronic acid and staining with crystal violet. Our data suggest that hyaluronic acid is able to interfere with bacterial adhesion to a cellular substrate in a concentration‐dependent manner, being notably active when assessed as pure substance. Moreover, we found that Staphylococcus aureus biofilm was more sensitive to the action of hyaluronic acid than biofilm produced by Haemophilus influenzae and Moraxella catarrhalis. In conclusion, hyaluronic acid is characterized by notable antiadhesive properties, while it shows a moderate activity against bacterial biofilm. As bacterial adhesion to oral cells is the first step for colonization, these results further sustain the role of hyaluronic acid in prevention of respiratory infections.